2000
DOI: 10.1074/jbc.275.17.12626
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein-β Regulates Interferon-induced Transcription through a Novel Element

Abstract: We have described previously a novel interferon (IFN)-responsive cis-acting enhancer element called ␥-IFN-activated transcriptional element (GATE). GATE is distinct from the known IFN-stimulated elements and binds to novel transacting factors. To identify the ␥-IFNresponsive transacting factors that interact with GATE, we have screened a cDNA expression library derived from IFN-␥-stimulated murine macrophage cell line and isolated three different cDNAs. Among these is a gene coding for the pleiotropic transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 40 publications
5
66
2
Order By: Relevance
“…In mammals, IFNc-induced IRF9 protein expression requires de novo protein synthesis, which results in the discovery of GATE motif-dependent induction of mouse IRF9 (Xiao et al, 1997a). A serial of studies revealed the underlying mechanism: initially, IFNc treatment induces the synthesis of two kinds of transcription factors, C/EBP-b and GBF1, possibly through JAK-STAT signaling pathway; subsequently, the produced transcription factors are activated by IFNc treatment, translocate to nucleus and bind to the GATE motif triggering IRF9 expression (Hu et al, 2002;Kalvakolanu and Roy, 2005;Meng et al, 2005;Roy et al, 2000;Xiao et al, 2001). Therefore, the signaling transduction involved is likely different between GAS-dependent and GATE-dependent induction of zebrafish IRF9 gene by zebrafish IFNc2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, IFNc-induced IRF9 protein expression requires de novo protein synthesis, which results in the discovery of GATE motif-dependent induction of mouse IRF9 (Xiao et al, 1997a). A serial of studies revealed the underlying mechanism: initially, IFNc treatment induces the synthesis of two kinds of transcription factors, C/EBP-b and GBF1, possibly through JAK-STAT signaling pathway; subsequently, the produced transcription factors are activated by IFNc treatment, translocate to nucleus and bind to the GATE motif triggering IRF9 expression (Hu et al, 2002;Kalvakolanu and Roy, 2005;Meng et al, 2005;Roy et al, 2000;Xiao et al, 2001). Therefore, the signaling transduction involved is likely different between GAS-dependent and GATE-dependent induction of zebrafish IRF9 gene by zebrafish IFNc2.…”
Section: Discussionmentioning
confidence: 99%
“…The expression property of mouse IRF9 correlates with the complexity of its promoter structure, which includes multiple potential regulatory elements including NF-jB, GAS, GATE (IFN-gamma-activated transcriptional element), and Myc/Max elements (Rani et al, 2010). GATE motif is first characterized in mouse IRF9 promoter as a binding site of CAAAT/enhancer binding protein-b (C/EBP-b) (Roy et al, 2000;Xiao et al, 1997aXiao et al, , 2001) and GATE-binding factor 1 (GBF1) (Hu et al, 2002;Meng et al, 2005) in response to IFNc treatment. Both C/EBP-b and GBF1 binding to GATE site significantly promotes IRF9 gene transcription (Meng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this construct a 74-bp element of murine p48 gene promoter, encompassing GATE, was cloned upstream of the simian virus 40 (SV40) early promoter driving luciferase. Mutagenesis of the GATE sequence in this construct caused a loss of IFN-␥ response and C͞EBP-␤ binding (8). The GATE-Luc and GATE-Mu constructs contained a single copy of wild-type and mutant GATE, respectively, cloned upstream of simian virus 40 minimal promoter in pGL3 promoter vector (7).…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of EGR-1 DNA binding activity was demonstrated by competition with wild-type but not mutant unlabeled probes (data not shown). Recent studies have revealed that C͞EBP-␤, a member of the CCAAT family of transcription factors, is induced by IFN-␥ in different tissues (7). Western analysis revealed that C͞EBP-␤ is induced by IFN-␥ in Stat1-null fibroblasts.…”
Section: Regulation Of Immediate-early and Chemokine Gene Expression Bymentioning
confidence: 99%
“…About a third of the genes induced by IFN-␥ in Stat1-null fibroblasts also are induced by IFN-␥ in wild-type cells. These include the transcription factors EGR-1, C͞EBP-␤, and LRG-21 (7,25,26), the cytoplasmic regulatory proteins SOCS-2 and SOCS-3 (27), the stress-response proteins metallothionein and PGHS-2 (28,29), osteopontin (30), and the secreted autocrine factor HB-EGF (29). Several genes are suppressed by IFN-␥ in Stat1-null fibroblasts (see Table 2, which is published as supplemental data on the PNAS web site, www.pnas.org).…”
Section: Identification Of Genes Regulated By Ifn-␥ In Serum-starved mentioning
confidence: 99%